2020
DOI: 10.1111/cen.14154
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between glucose metabolism and serum steroid hormones in patients with polycystic ovary syndrome

Abstract: Objective Polycystic ovary syndrome (PCOS) is associated with an increased prevalence of dysglycaemia, which includes impaired glucose tolerance and type 2 diabetes mellitus (T2DM). Patients with PCOS demonstrate abnormal patterns of steroid hormones. Here, we analyse the correlation between glucose metabolism and serum steroid hormones in PCOS. Design Observational double‐centre study. Patients 914 patients with PCOS. Measurements We assessed the glucose metabolism status of all patients according to the 1999… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Ovarian follicular development is a highly coordinated and nutrition-sensitive process [ 23 ], and glucose is an important energy substrate for metabolism in the follicles of many species [ 24 , 25 , 26 , 27 ]. Previous studies confirm that short-term dietary supplementation of ewes during the luteal phase can increase fertility due to elevated glucose and steroid hormone concentrations in follicles [ 19 , 28 , 29 ], whereas glucose has deleterious effects on ovary structure and function at higher concentrations [ 5 , 30 , 31 ]. Our previous study also demonstrated that glucose dose had a significant effect on GCs function, with 8.4 mM representing the optimal glucose concentration for GCs to secrete steroid hormones in vitro and a higher concentration of glucose (33.6 mM) inhibiting GCs proliferation and steroidogenesis [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian follicular development is a highly coordinated and nutrition-sensitive process [ 23 ], and glucose is an important energy substrate for metabolism in the follicles of many species [ 24 , 25 , 26 , 27 ]. Previous studies confirm that short-term dietary supplementation of ewes during the luteal phase can increase fertility due to elevated glucose and steroid hormone concentrations in follicles [ 19 , 28 , 29 ], whereas glucose has deleterious effects on ovary structure and function at higher concentrations [ 5 , 30 , 31 ]. Our previous study also demonstrated that glucose dose had a significant effect on GCs function, with 8.4 mM representing the optimal glucose concentration for GCs to secrete steroid hormones in vitro and a higher concentration of glucose (33.6 mM) inhibiting GCs proliferation and steroidogenesis [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Li et al ( 9 ) indicated that propofol inhibited colorectal cancer cell viability and metastasis by regulating the miR-124-3p.1/AKT3 axis. PCOS is a common endocrine disorder with approximate incidence of 10% in women worldwide ( 1 ). The common clinical manifestations of PCOS include hyperandrogenemia, chronic anovulation and sclerocystic ovaries ( 2 , 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is a universal endocrine disorder, with an incidence of 5-10% in women of childbearing age globally ( 1 , 2 ). The major clinical symptoms in patients with PCOS are subfertility, amenorrhea, seborrhea and acanthosis ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the exact mechanisms underlying the development of PCOS are not fully understood, genetics and environmental factors are believed to play signi cant roles 12 . Genetic factors may contribute to abnormal insulin signaling, leading to insulin resistance and metabolic disturbances in patients with PCOS 13,14 . Environmental factors, such as an unhealthy diet and lifestyle, may also contribute to PCOS development.…”
Section: Introductionmentioning
confidence: 99%